2020
DOI: 10.1002/mde.3164
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain finance: A three‐party decision model with suppliers' guarantees for retailers

Abstract: Under the premise that financing constraints frequently occur in the supply chain, this paper investigates the financing model of the supplier providing guarantee for the retailer under symmetric and asymmetric information. The optimal solutions of the retailer, the supplier, and the bank are studied by using the Stackelberg game. Results show that increasing the supplier's guarantee proportion can effectively improve the bank's reasonable margin rate and increase the supplier's profit. Under the condition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Yan et al studied the optimal guarantee mechanism of banks, retailers, and suppliers in supply chain finance with the Stackelberg game method [14]. Yan et al analyzed the effect of risk aversion on the cooperative strategies of banks, manufacturers, and retailers in supply chain finance [15].…”
Section: Relationship Of Participants In Supply Chain Financementioning
confidence: 99%
“…Yan et al studied the optimal guarantee mechanism of banks, retailers, and suppliers in supply chain finance with the Stackelberg game method [14]. Yan et al analyzed the effect of risk aversion on the cooperative strategies of banks, manufacturers, and retailers in supply chain finance [15].…”
Section: Relationship Of Participants In Supply Chain Financementioning
confidence: 99%
“…However, the former research results are mostly based on the methods of financial ratio analysis, regression model analysis, and propensity score matching evaluation (Oh et al, 2009 ), which tend to ignore the dynamic changes of guarantee market and the interaction of business behaviors between guarantee subjects. Therefore, some scholars explored the operation behavior of financing guarantee institutions (He et al, 2014 ), financing equilibrium under the effect of credit guarantee (Yan et al, 2016 ; Wang et al, 2022 ), and factors influencing equilibrium efficiency (Yan et al, 2017 , 2020 ) within the completely rational traditional game framework.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The studies found that the after‐sales service program aimed at maximizing profits does not match the level of customer satisfaction. Yan et al (2020) analyzed the situation that suppliers provide retailers with guaranteed financing services; the results shown that when the proportion of supplier guarantees increases, the bank's margin rate and the supplier's profit will also increase. Hong et al (2019) analyzed the performance of CLSCs in different service structures.…”
Section: Literature Reviewmentioning
confidence: 99%